ANALYSIS OF PROCEDURE FOR COLLECTION, DEPOSITION AND REPORTING OF VALUE ADDED TAXES (VAT) IN. WAHANA INTERFOOD ARCHIPELAGO - Alamanda, Amelia Rizky (Jurnal Ekonomi dan Bisnis, 2018)
Value Added Tax (VAT) is one type of indirect tax on the addition of a taxable goods or service collected by a taxable entrepreneur to the final consumer in the customs area. The object of this research is the assessment of Value Added Tax (VAT) in PT. Wahana Interfood Nusantara, using a descriptive approach, with data collection techniques by interview and direct observation. Based on research that has been done, it can be concluded that PT. Wahana Interfood Nusantara has carried out the collection of Value Added Tax in accordance with the applicable laws and regulations, which can be seen by using the e-Invoicing application as a means of collecting Value Added Tax